Use of Cyclosporine and Itraconazole as Palliative Treatment for Proventricular Dilatation Disease in Psittacine Birds - Laura M. Kleinschmidt; Sharman M. Hoppes; Jeffrey M. B. Musser; Ian Tizard; J. Jill Heatley (Veterinary Sciences)
Proventricular dilatation disease (PDD) is a neurologic syndrome of birds caused by the infectious agent Psittacine Bornavirus (PaBV). Clinical disease may be based on the T-cell-mediated immune response to PaBV within the central and peripheral nervous system, similar to Borna disease virus, a closely related mammalian virus. Lymphoplasmacytic infiltrations may occur in ganglia, nerve plexuses, peripheral nerves and the central nervous system of the infected bird. Clinical disease may result in multiple neurologic disorders and life-threatening morbidity. Treatment of PDD with antivirals and non-steroidal anti-inflammatories has thus far been non-curative and unsuccessful long-term. Cyclosporine is an immunosuppressant drug that decreases cell-mediated immune responses by inhibiting T-cell proliferation and decreasing cytokine production. In avian species, cyclosporine is a potent immunosuppressant with T-cell-specific action. A pilot study performed in PaBV-infected cockatiels showed increased weight gain and a lack of morbidity or mortality following experimental PaBV infection and cyclosporine treatment at 10 mg/kg orally every 12 h. In this case series of six psittacine birds affected by PDD, cyclosporine at this dose alleviated or reduced clinical signs in multiple birds without severe sequelae. Itraconazole was used concurrently in these cases to prevent secondary fungal infections during immunosuppression but may have had a synergetic effect when used in combination with cyclosporine. Further prospective research is indicated to better evaluate cyclosporine use in birds with PDD. However, these preliminary clinical findings suggest that cyclosporine and itraconazole administration is a treatment option for palliation of PDD in psittacine patients, especially those refractory to other treatments.